The mockingbird's song [large type] - Brunstetter, Wanda E. (Brunstetter, Wanda E. Amish greenhouse mystery, 2020)
"Sylvia has been nearly paralyzed with grief and anxiety since the tragic death of her husband, father, and brother in a traffic accident. She tries to help in the family's greenhouse while caring for her two children, but she prefers not to have to deal with customers. Her mother's own grief causes her to hover over her children and grandchildren, and Sylvia seeks a diversion. She takes up birdwatching and soon meets an Amish man who teaches her about local birds. But Sylvia's mother doesn't trust Dennis Weaver, and as the relationship sours, mysterious attacks on the greenhouse start up again." -- Back cover